The size of a smell: assessment of rival's relative size from femoral secretions in the common wall lizards, Podarcis muralis (Laurenti, 1768). (23rd January 2023) - Scali, Stefano; Sacchi, Roberto; Gozzo, Elisabetta; Chiesa, Stefano; Coladonato, Alan J; Zuffi, Marco A L; Mangiacotti, Marco
Abstract: Animal communication depends on signals conveying information to a receiver who must perceive and decode them. Signals involved in territoriality are usually complex stimuli that should be correctly interpreted to avoid unnecessary conflicts. Lacertids use both visual and chemical stimuli in modulating their aggressive response against conspecifics and the rival's size is one of the most important information, affecting the success probability in combat. To assess the actual ability of decoding information about a rival's size based on its chemical stimulus alone, 60 males of Podarcis muralis were tested for three consecutive days in an arena bearing a mirror (to simulate an equal-sized intruder), and the chemical cues (femoral secretions) from an unknown individual of different size. Significant differences were observed in tongue-flicks number, which grew as the size difference between the focal lizard and the secretion donor decreased. This can be interpreted as the need for the lizard to better evaluate the potential competitor's characteristics. The size difference also affected the number of bites against the mirror. They increased when the size of the focal lizard was larger than the donor triggering the aggressive response with a higher probability of winning the contest. This confirms that the focal lizard had correctly decoded the information about the opponent's size by chemical stimulus. Although previous studies have shown that some components of the chemical signals are potentially informative about the signaler's size, this is the first demonstration that male P. muralis is actually able to decode and use such information. Abstract : Lizards communicate through chemical signals, which convey information about the signaller' quality and identity. We demonstrate that males can perceive and decode information about actual rival's size using chemical cues, even when they see a size-matched mirrored image. Individuals attack smaller rivals more often, but spend the most time assessing rivals when their opponents are of similar size, and less time assessing rivals when they are substantially smaller or larger than them. This could be useful to avoid unnecessary and costly fightings with stronger opponents.